The Effect of Organizational Inertia and Customer Orientation with Incremental Innovation as the Mediating Variable towards Organizational Performance - Hongdiyanto, Charly; Widyarini, Lydia Ari; Yusup, Adi Kurniawan (Universitas Ciputra Surabaya, 2022)
The purpose of this study was to find out the relationship between Organizational Inertia, Customer Orientation, Incremental Innovation and Organizational Performance. The sample used in this study were 180 MSME companies spread across East Java. The reason MSMEs are used in this study is related to the concept of organizational inertia that is attached to small-scale companies. From this study it was found that incremental innovation is not a mediating variable that links organizational inertia and customer orientation with organizational performance.